2019
DOI: 10.1002/minf.201900007
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Some General Molecular Descriptors of Saturated Hydrocarbons

Abstract: Three general molecular descriptors, namely the general sum-connectivity index, general Platt index and ordinary generalized geometric-arithmetic index, are studied here. Best possible bounds for the aforementioned descriptors of arbitrary saturated hydrocarbons are derived under certain constraints. These bounds are expressed in terms of number of carbon atoms and number of carboncarbon bonds of the considered hydrocarbons.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Liu et al [33] investigated and identified proteins having nucleotide-binding activity using star graph TIs. Ali et al [34,35] and Du et al [36] studied and applied some degreebased TIs such as the first Zagreb connection index, ordinary generalized geometric-arithmetic index, general Platt index, and general sum-connectivity index to establish extremal results for alkanes. Hayat et al [37] performed comparative testing of certain chemical structures (carbon nanotubes, carbon nanocones, and tetrahedral diamond) using various degree-based TIs.…”
Section: Journal Of Chemistrymentioning
confidence: 99%
“…Liu et al [33] investigated and identified proteins having nucleotide-binding activity using star graph TIs. Ali et al [34,35] and Du et al [36] studied and applied some degreebased TIs such as the first Zagreb connection index, ordinary generalized geometric-arithmetic index, general Platt index, and general sum-connectivity index to establish extremal results for alkanes. Hayat et al [37] performed comparative testing of certain chemical structures (carbon nanotubes, carbon nanocones, and tetrahedral diamond) using various degree-based TIs.…”
Section: Journal Of Chemistrymentioning
confidence: 99%
“…Details about the chemical applications of the variable Randić index can be found in [5,7,9,12,[15][16][17][18][19][20][21][22] and related references listed therein. It needs to be mentioned here that the variable Randić index seems to have more chemical applications than the several well-known variable indices, for example, the indices considered in [23][24][25][26][27][28][29][30][31][32][33]. However, to the best of the authors' knowledge, mathematical properties of the variable Randić index, for c > 0, have not yet been discussed explicitly in any paper.…”
Section: Introductionmentioning
confidence: 99%
“…In [18], a mathematical study of the variable Randić index was initiated and it was proved that the star graph has the minimum variable Randić index among all trees of a fixed order n, where n ≥ 4. It needs to be mentioned here that the variable Randić index seems to have more chemical applications than the several wellknown variable indices, see, for example, the variable indices considered in the papers [19][20][21][22][23][24][25]. For convenience, we introduce some further notation and terminology.…”
Section: Introductionmentioning
confidence: 99%